HUBUNGAN PENGETAHUAN PASIEN DAN DUKUNGAN KELUARGA DENGAN KEPATUHAN DIET PADA PASIEN PENYAKIT JANTUNG KORONER DI POLIKLINIK JANTUNG RSUP dr. SOERADJI TIRTONEGORO KLATEN - Lily Nurcahyani; Herni Astuti; Siti Wahyuningsih (Medika Respati : Jurnal Ilmiah Kesehatan, 2021)
Relationship Between Patient Knowledge And Family Support With Dietary Compliance On Coronary Heart Disease Patients In Cardiovaskular Polyclinic Dr. Soeradji Tirtonegoro KlatenBackground: Coronary heart disease (CHD)  is caused by hardening of the arteries due to accumulation of fat in the arteries that supply blood to the heart. CHD is increasing and be the number one cause of death in the world. One of CHD prevention efforts is with diet therapy. Dietary compliance is influenced by several factors, including knowledge and family support. Objectives: :  to determine relationship between patient knowledge and family support with dietary compliance on coronary heart disease patients in Cardiovaskular Polyclinic   dr. SoeradjiTirtonegoro Klaten. Methods: design of this study was observational with cross sectional approach. The sample in this study according to inclusion and exclusion criteria amounted to 138 respondents with purposive sampling as a sampling technique. The research instrument used a questionnaire with interview method. The statistical test used to analyze the relationship between variables with chi-square test or Fisher's Exact test as an alternatives. Results: the results showed that most respondents had a good knowledge on CHD (85,5%), good family support (89,9%), compliance on fat consumption (69,6%) and compliance on fiber consumption (10,9 %). Conclusion: there was  no relationship between patient knowledge and complience on fat and fiber consumption. There was no relationship between family support with compliance on fat and fiber consumption (p> 0,05).